Effect of inoculation of vesicular arbuscular mycorrhiza on horsegram (Macrotyloma uniflorum) grown in soil in iron-mine area - Pattanaik, R; Sahu, S; Padhi, G S; Mishra, A K (The Indian Journal of Agricultural Sciences, 2012)
A nursery experiment was carried out during rainy season of 1989-90 to study the effect of inoculation of 2 vesicular arbuscular mycorrhizac (VAM). viz Glomus fasciculatum (Thaxt. sensu Gerd.) Gerd. & Trappe and G. mosseae (Nic. & Gerd.) Gerd. & Trappe, on the growth, nodulation and productivity of horsegram [Macrotyloma uuniflorum (Lam.) Verdcourt] grown in soil in the iron-mine area. Both the VAM fungi showed increase in growth and nodulation at 30 and 60 days after plant growth, especially at the latter stage. Inoculation with G.fasciculatum at 60 days after plant growth led to maximum increase in shoot height (36.03 %). dry weight of plant (94.44%), fresh weight (75%) and dry weight (100%) of nodules, and dry weight of seeds (27.45%).